2020
DOI: 10.1186/s13023-020-1300-5
|View full text |Cite
|
Sign up to set email alerts
|

Finnish gelsolin amyloidosis causes significant disease burden but does not affect survival: FIN-GAR phase II study

Abstract: Background: Hereditary gelsolin (AGel) amyloidosis is an autosomal dominantly inherited systemic amyloidosis that manifests with the characteristic triad of progressive ophthalmological, neurological and dermatological signs and symptoms. The National Finnish Gelsolin Amyloidosis Registry (FIN-GAR) was founded in 2013 to collect clinical data on patients with AGel amyloidosis, including altogether approximately one third of the Finnish patients. We aim to deepen knowledge on the disease burden and life span of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…In a recent study, Schmidt et al presented a comprehensive list of multiple ophthalmological symptoms. Here, they quantify the frequency of drooping eyelids due to cutis laxa and facial nerve paresis in patients in about 86 % (n = 261), yet BC is not explicitly described [9]. With this report we can confirm and highlight BC as a possible lateonset manifestation of AGel amyloidosis.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In a recent study, Schmidt et al presented a comprehensive list of multiple ophthalmological symptoms. Here, they quantify the frequency of drooping eyelids due to cutis laxa and facial nerve paresis in patients in about 86 % (n = 261), yet BC is not explicitly described [9]. With this report we can confirm and highlight BC as a possible lateonset manifestation of AGel amyloidosis.…”
Section: Discussionmentioning
confidence: 59%
“…Still, a curative therapy is not available yet and repeated surgeries may be needed. Depression is frequently found as a comorbidity in AGel patients, mainly due to the limitation of facial expressions and the appearance of premature aging [9]. Thus, psychological support should also be considered as part of a holistic approach to improve the quality of life of AGel patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular and systemic features of Finnish Amyloidosis were evident in both families with individuals manifesting cutis laxa, dermatochalasis, dry eyes, and eczema. Although little data is available on other systemic manifestations of Finnish Amyloidosis in the literature, a recent study reported a high prevalence of hypothyroidism (10%) and cardiac arrhythmias (15%), which were noted in Family 2 (Schmidt et al, 2020). On the basis of lack of GSN staining in lung and canalicular biopsy specimens, we consider it unlikely that the benign inflammatory polyp and chronic dacryocystitis in Case 2 were direct results of pathological GSN deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloidosis of the Finnish type (MIM# 105120) also known as Finnish Amyloidosis, is a rare autosomal dominant disease characterized by specific systemic and ophthalmic features resulting from pathological tissue deposition of amyloidogenic gelsolin (GSN) proteins (Maury et al, 1990). Although Finnish Amyloidosis is characterized by multiple systemic features caused by extracellular aggregation of aberrant protein fragments, this disease most notably results in ocular features, including sight‐affecting corneal dystrophy, dry eyes, chronic corneal ulceration, and an increased risk of cataracts and glaucoma (Schmidt et al, 2020). The integumentary and nervous systems are also commonly affected, with a high incidence of cutis laxa, dermatochalasis, dry skin, and facial nerve palsies.…”
Section: Introductionmentioning
confidence: 99%